Size-dependent structural behaviors of crumpled graphene sheets. (15th April 2021) - Liao, Yangchao; Li, Zhaofan; Fatima,; Xia, Wenjie
Abstract: Understanding the complex structural behaviors of crumpled graphene at a fundamental level is of critical importance in various engineering and technological applications. Here, we present a coarse-grained molecular dynamics (CG-MD) study for investigating structural behaviors of graphene sheets having varying sizes (or masses) during the crumpling process. The simulation results reveal that larger size graphene sheets at the initial two-dimension (2D) state tends to become more self-adhering and self-folding upon crumpling compared to the smaller ones, before forming a sphere-like highly crumpled structure. The fractal dimension of the crumpled graphene sheets, i.e., a measure of packing efficiency, is predicted to be D = 2.395 from our CG modeling, which is largely consistent with previous measurements. Remarkably, the size-dependence of various structural properties of the crumpled graphene sheets, including radius of gyration, hydrodynamic radius, and viscosity radius, can be quantitively described by the power-law scaling relationships during the crumpling process. By systematically evaluating shape descriptors, it is found that the overall crumpling behaviors of graphene sheets can be characterized by three different regimes ( i.e., less, intermediate, and highly crumpled states), which are associated with edge-bending, self-adhesion, and further compression mechanisms, respectively. Our study provides fundamental insights into the size-dependent structural behavior of graphene sheets under crumpling, which is crucial to develop the structure-property relationships towards designing and engineering crumpled matter. Graphical abstract: Image 1